2020
DOI: 10.3390/ani10112185
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus dysgalactiae—Contagious or Environmental?

Abstract: Streptococcus dysgalactiae is among the most important pathogens causing bovine mastitis. Unfortunately, there is presently a lack of clear knowledge about the mode of transmission—contagious or environmental—of this pathogen. To obtain more information on this, knowledge of the genetic diversity of the isolated microorganisms at the farm level can be useful. To observe the strain variety in different herds of cattle, isolates of Strep. dysgalactiae were collected from clinical mastitis samples at different fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 14 publications
1
19
0
1
Order By: Relevance
“…It also showed that the same SDSD strain caused IMI in multiple cows in the same herd. Similar findings have been described by others (Lundberg et al, 2016;Wente and Krömker, 2020) and can be taken as evidence of direct or indirect transmission between animals. Further studies are needed to determine whether some strains of SDSD have greater potential for contagious spread than others.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It also showed that the same SDSD strain caused IMI in multiple cows in the same herd. Similar findings have been described by others (Lundberg et al, 2016;Wente and Krömker, 2020) and can be taken as evidence of direct or indirect transmission between animals. Further studies are needed to determine whether some strains of SDSD have greater potential for contagious spread than others.…”
Section: Discussionsupporting
confidence: 90%
“…Using various strain-typing schemes, previous studies have suggested that the strain diversity, and hence also the epidemiology of SDSD, may differ between farms. For example, several different SDSD genotypes can be found in individual dairy farms, as might be expected for opportunistic bacteria (Gillespie et al, 1998;Wang et al, 1999;Lundberg et al, 2016;Wente and Krömker, 2020). However, the same studies also showed that in some herds one strain dominated and could be found in milk from multiple cows.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…For S. dysgalactiae , the classification in environmental or contagious is not clear. Due to its ability to survive within the host and in the environment, it is described as an intermediate pathogen [ 16 ]. The majority of S. dysgalactiae strains are non-hemolytic, although alpha-hemolytic exceptions exist.…”
Section: Classificationmentioning
confidence: 99%
“…Streptococcus dysgalactiae is able to endure within the host and in the environment, this uncertainty makes this bacteria counted as an intermediate pathogen [28]. Furthermore, S. dysgalactiae generally concurrent with the infectious problem in bovine and other ruminants.…”
Section: Streptococcus Virulence Factorsmentioning
confidence: 99%